EFEKTIVITAS UNIT LAYANAN ADUAN SURAKARTA DALAM MENERIMA KELUHAN WARGA DI KOTA SURAKARTA - Is Hadri Utomo; Retno Suryawati; Herwan Parwiyanto (NATAPRAJA, 2019)
The establishment of the Surakarta Complaint Service Unit (ULAS) in 2013 as a non-structural government organization unit that carried out public complaints services. ULAS was formed to improve service quality and ensure the provision of public services in accordance with the principles of good governance, including the realization of public information disclosure in response to complaints from people who are not satisfied with the services they receive. This study examines the effectiveness of ULAS in accepting citizen complaints and the steps of the Surakarta City Government to follow up on these complaints, as well as solutions. All results state the existence of effectiveness, with some special notes on the conditions or variable questions that have answers that do not agree, among others concerning: the target of resolving citizen complaints by ULAS, complaints of citizens against certain problems have not been channeled to more than one OPD, solving problems against Complaints have also not fulfilled the satisfaction and aspirations of citizens, and related infrastructure facilities have not been in line with the development of information technology. Some of these are specific notes regarding the organizational effectiveness of ULAS.